A Monopolist in Public Transport: Undersupply or Oversupply? - Vladimir A. Karamychev; Peran van Reeven (Tinbergen Institute, 2009)
A monopolist in public transport may oversupply frequency relative to the social optimum, as van Reeven (2008) demonstrates with homogeneous consumers. This result generalizes for heterogeneous consumers who know the timetable. Whether a monopolist oversupplies or undersupplies frequency depends on the degree of consumers' heterogeneity as reflected in the distribution of consumers' reservation prices. Oversupply is likely to occur when this distribution is peaked, and undersupply is likely to occur when this distribution is rather flat. In particular, monopoly production results in the oversupply of frequency when consumers' reservation prices are concentrated around the entry costs of the private car, being the main alternative to public transport.
Keywords: D42; L12; L91; 330; Frequency oversupply; Mohring effect; transportation monopolist; Öffentlicher Nahverkehr; Staatsmonopol; Skalenertrag; Zeitökonomie; Theorie